Corticotropin releasing hormone in colonic mucosa in patients with ulcerative colitis. Issue 4 (October 1995) - Kawahito, Y; Sano, H; Mukai, S; Asai, K; Kimura, S; Yamamura, Y; Kato, H; Chrousos, G P; Wilder, R L; Kondo, M
Abstract : Corticotropin releasing hormone (CRH) is a key hormone in integrated response to stress, acting as the major regulator of the hypothalamic-pituitary-adrenal axis. Recently, local production of CRH has been detected in normal human colonic enterochromaffin cells. CRH is locally secreted in granulomatous and arthritic tissues in rats and humans, where it seems to act as a local proinflammatory agent. To find out if CRH is present in colonic tissues of patients with ulcerative colitis, this study examined the expression of this peptide in the large bowel of patients with ulcerative colitis. Colonic tissues of patients with ulcerative colitis obtained by endoscopic biopsy were immunostained with anti-CRH antibody. CRH messenger (m) RNA was also examined in biopsy specimens of ulcerative colitis by the reverse transcribed polymerase chain reaction method and by in situ hybridisation. Considerably enhanced expression of immunoreactive CRH was found in mucosal inflammatory cells. Intense staining with anti-CRH antibody was also shown in mucosal macrophages. CRH mRNA was expressed in mucosal epithelial cells. The expression of immunoreactive CRH in colonic mucosal epithelial cells of ulcerative colitis slightly increased, but not significantly, compared with normal colonic mucosal epithelial cells. These results suggest that CRH may play a part in the modulation of intestinal immune and inflammatory system, and as a modulator in the pathogenesis of ulcerative colitis.